1974
DOI: 10.1111/j.1748-1716.1974.tb05632.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Design and Reactivity of Series‐coupled Vascular Sections in Spontaneously Hypertensive Rats (SHR)

Abstract: In a series of studies (cf. Folkow et al. 1973) the design, and reactivity, of the resistance vessels in hypertension has been hemodynamically analyzed, comparing constant flow perfusion of, preferentially, the hindquarter vascular beds of hypertensive (SHR) and paired normotensive control rats (NCR). Measurements of the resistance at maximal dilatation, the 'threshold sensitivity' to noradrenaline (NA), the entire dose-response curve to NA and its steepness, and the maximal pressor response to supramaximal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
1

Year Published

1976
1976
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 2 publications
(2 reference statements)
7
41
1
Order By: Relevance
“…42 However, drastic and rapid pressure reductions may then more easily cause relative ischemia in brain and myocardium, because the amplifier properties and the raised R,^ will then cause more profound flow reductions. Otherwise, it is when precapillary structural adaptation encompasses all systematic circuits, as in hypertension, that it has deleterious long-term consequences, mainly because it then invites to the positive feedback interactions discussed earlier.…”
Section: Site Of Adaptation and Nature Of Stimulusmentioning
confidence: 99%
See 2 more Smart Citations
“…42 However, drastic and rapid pressure reductions may then more easily cause relative ischemia in brain and myocardium, because the amplifier properties and the raised R,^ will then cause more profound flow reductions. Otherwise, it is when precapillary structural adaptation encompasses all systematic circuits, as in hypertension, that it has deleterious long-term consequences, mainly because it then invites to the positive feedback interactions discussed earlier.…”
Section: Site Of Adaptation and Nature Of Stimulusmentioning
confidence: 99%
“…It is, however, likely that the pressure-induced changes in wall stress, together with the flow-dependent changes in chemical environment, activate appropriate local growth-modulating factors that, in the final analysis, direct the complex changes of vascular design. 2829 This local remodeling of the precapillary resistance vessels provides the basis for a long-term autoregulation of blood flow and of capillary pressure ("structural autoregulation" 42 as a correlate to short-term functional autoregulation). Thus, both are locally induced and both tend to keep flow and, far more importantly, capillary pressure constant during changes in MAP.…”
Section: Site Of Adaptation and Nature Of Stimulusmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the number of patent precapillary arterioles is actually decreased in skeletal muscle of SHR. 28 Therefore, one might expect the number of patent postcapillary vessels to decrease to maintain tissue homeostasis. Hutchins * that R v is reduced in SHR hindparts and cremaster muscle, respectively.…”
mentioning
confidence: 99%
“…Following local chemical sympathetic denervation with 6-hydroxydopamine, VSM in SHR hyperpolarized from a control value of -37 ± 0.6 to -51 ± 0.4 mV while E ra in WKY remained at -5 0 ± 0. N the spontaneously hypertensive rat (SHR), the elevated total peripheral resistance (TPR) accompanying development of hypertension has been attributed to: 1) structural adaptations in the arterial vessel wall 1 and the microvessel network, 2 and 2) increased vascular smooth muscle (VSM) tone. In turn, this elevated tone has been attributed to an elevated sympathetic neural input 1 4 and to alterations in the intrinsic mechanisms of the VSM membrane that regulate the concentration of cytosolic activator calcium (Ca).…”
mentioning
confidence: 99%